Firefly Lane - Hannah, Kristin (New York : St. Martin's Griffin, 2009)
Inseparable best friends Kate and Tully, two young women who, despite their very different lives, have vowed to be there for each other forever, have been true to their promise for thirty years, until events and choices in their lives tear them apart.
"A novel"--Dust jacket.
Keywords: Best friends -- Fiction; Friendship in adolescence -- Fiction; Female friendship -- Fiction; Nineteen seventies -- Fiction; Bildungsromans